Sentencing Disparities in Judicial Considerations of Electronic Sexual Violence Cases - Nazrin, Mohamad; Prasetyo, Bayu; Elviandri, Elviandri (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Indonesia, as a state governed by the rule of law, upholds equality before the law and the protection of human rights as fundamental principles. However, the rapid development of digital technology has created new challenges, particularly the emergence of electronic sexual violence, which has raised significant public concern. Although Law Number: 12 of 2022 regulates such crimes, judicial practice reveals sentencing disparities that undermine legal certainty and victim protection.Purposes of the Research: This study aims to analyze the causes of judicial sentencing disparities in cases of electronic sexual violence and examine their implications for law enforcement in Indonesia.Methods of the Research: The research employs a normative juridical method with a library research approach. Data were collected from primary legal materials such as statutory regulations, secondary legal materials including literature, doctrines, and previous studies, as well as tertiary legal materials such as legal dictionaries and encyclopedias.Findings of the Research: The findings indicate the existence of disparities in three court decisions that applied similar provisions but resulted in significantly different sentences. Factors contributing to these disparities include differences in judicial interpretation, the application of individualized sentencing principles, and non-juridical considerations. Such disparities have serious implications, including diminished legal certainty, reduced deterrence for offenders, weakened victim protection, and declining public trust in the judiciary. Therefore, the establishment of consistent, transparent, and victim-oriented sentencing guidelines is essential to ensure substantive justice in Indonesia’s criminal justice system.